Screening of osmotolerant micro organisms in the dried salted fish sold in kanyakumari district, tamilnadu - V, Mary Kensa; M, Anju (Kongunadu Research Journal, 2020)
Fish is one of the most important sources of animal protein available in the tropics and has been widely accepted as a good source of protein and other elements for the maintenance of healthy body. Salting and drying is an ancient and simple method to preserve fish and in India about 17% of the total catch is being used for salting and drying. The present investigation was aimed to analyse the presence of osmotolerant microbes in the dry fishes. The commercially important marine edible salted dry fishes were collected from the study area Pallam. Four common edible dry fishes like (Nethili, Sardines, Ribbon fish and Prawn) were selected for the screening of microbial population. The highest TFC value was reported in Sardine and Ribbon fish (5103) than the other fishes like Netthili and Prawn (4103 and 2103). The moisture content was higher (45%) in Prawn followed by Ribbon fish (40%), Sardines (29%), Netthili (26%). In this study,Prawn had high moisture content (45%) and high microbial load (5.3104 cfu/g). Total five fungal species were isolated from the selected dried fishes. The result of isolation of human pathogens such as Salmonella and Vibrio identified from the selected dry fish samples. The nutritive value of raw fish in found to be good.The sensory characteristics such as colour, odor, texture, insect infestation showed that the Sardine and Prawn was good in quality, while the netthili had decreased the quality. The study showed that salted and sundried fishes sold in study area are contaminated with pathogenic bacteria and fungal agents. Spoilage of dried fish products was found and this might be due to unhygienic handling of the fisher folks, improper processing and unhygienic vendors and vending areas.